Modernpracticesinnon-formaleducationas a toolforpreparingyouthtoworkwithmigrantandrefugeechildrenaspartoftheDP5YOUproject - Galan, Yaroslav; Yarmak, Olena; Hutsuliak, Liliana (My University, 2026)
This article presents the results of the project “Digital Platform of Knowledgeand Skills Development for Youth Working with Child Migrants and Refugees at the EuropeanLevel” (DP5YOU), co-funded by the European Union under the Erasmus+ program. It aims todevelop and implement innovative tools to train youth (youth workers) for social work in thecontext of martial law and the migration crisis. The relevance of the study stems from the needto identify effective non-formal education methods for the professional training of youthcapable of working with displaced children and refugees in Ukraine and the EuropeanUnion.Thepurposeoftheresearch is to provide a theoretical foundation and practicaldevelopment of the concept of a digital platform as a tool for the non-formal education of youth(youth workers) to ensure their effective work with vulnerable groups of children.Results. Atotal of 78 respondents participated in the study, including 42 girls and 36 boys. The studyfound that only 34.6 % of the respondents had experience participating in youth projects,indicating significant potential for increasing youth civic engagement. At the same time, mostrespondents are familiar with the concept of non-formal education and demonstrate awillingness to organize activities for vulnerable groups of children. Among the prioritycompetencies that need to be developed through non-formal education, leadership and careerskills were identified by 46.2 %, European values by 33.3 %, digital skills by 33.3 %, and environmental awareness by 10.2 %. Young people’s interest in digital learning formats–specifically videos (55.1 %), flipbooks (53.8 %), and online platforms (44.9 %)–formed thebasis for developing the concept of a digital platform. An important result obtained during theanalysis of the responses is the high level of readiness among young people for practicalactivities; 82.1 % of respondents expressed a desire to participate in organizing events, whichconfirms the feasibility of developing innovative training tools within the DP5YOU project.Conclusions. The findings of this study confirm the relevance of using modern non-formaleducation practices as an effective tool for preparing youth to work with vulnerable groups ofchildren. It was found that despite insufficient engagement in youth projects, young peopledemonstrate high motivation to participate in practical activities and a willingness to organizeevents. The scientifically grounded and well-developed concept of the digital platform is a keyinnovation of the project, fostering synergy between the theoretical training and practical workof youth workers. Priority competencies and a demand for blended learning formats have beenidentified, which justifies the feasibility of implementing innovative educational tools,particularly flipbooks, within the DP5YOU project.
Keywords: project; digitalization of education; professional competencies; migrant children; refugees; flipbooks; DP5YOU